Hemihypertrophy of the tongue in a newborn. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
A 2-month-old baby was first observed due to suspected lymphangioma of the tongue present since birth (Fig. 1). The baby was born at term by natural delivery, with a weight of 3.550 and a height of 56 cm, Apgar scores at 1 and 5 minutes respectively 9 and 10. The family history was negative for malformations, physical examination of the skin and other organs was normal except for a compound fracture of the right clavicle. The tongue, which was asymmetric due to hypertrophy of the right half (Fig. 2, 3), showed no other alterations. On palpation the thickness of the right half was the double of the left half. A cranial MRI showed cerebral findings within normal limits and hypertrophy of the tongue body on the right half without signal abnormalities or signs of abnormal enhancement after administration of contrast medium. The final diagnosis was hemihypertrophy of the tongue.